Mobile only users powered by fixed-mobile substitution - Julienne Liangy; Marc Petulowa (International Telecommunications Society (ITS), 2012)
In a context of partial fixed-mobile substitution, we analyze fixed-mobile bundling and mobile-to-fixed off-loading in a duopoly model in which consumers buy one or two products. A joint purchase discount mitigates fixed-mobile substitutability and consequently reduces mobile-only and fixed-only consumers. Practises like introducing a small discount, applied on a bundle of multiple service or mobile-to-fixed offloading by both operators are analysed. We find that such practises do not have negative impacts on the profits of whole market and lead to both consumers' surplus and welfare gains. The investment incentives in fixed network are positive and can be boosted by FM bundling without considering regulatory intervention and before taking into account of fixed costs. The investment incentives in mobile network are more likely a situation of prisoners' dilemma where operators should invest as long as there are mobile-only consumers.
Keywords: 330